Effects of ethics communication in health care: a cluster randomised controlled trial - Brännström Margareta; Isaksson Ulf; Fischer Grönlund C. (BMC Medical Ethics)
Abstract Background Studies show that healthcare professionals encounter ethically difficult situations in everyday clinical practice, and there is a need for interprofessional communication in organised forms. Ethics communication in groups (ECG), based on Habermas’s theory of communicative actions, is a form of support for interprofessional communications about ethical issues. The ‘one to five method’ is a practical tool for healthcare professionals with education in ethics to facilitate ECG in everyday clinical practice. Research aim To evaluate the effects of organised ECG using the ‘one to five’ method for health care professionals concerning moral distress and ethical climate at wards with round-the-clock care compared with a control group. Research design This was a prospective cluster randomised study with an open, non-blinded design. Methods Nine wards with different medical specialisations at one university hospital were purposefully and then randomly allocated to an intervention group (IG) (n = 5) and a control group (CG) (n = 4). An ECG was performed monthly for six months in the intervention group. Prospective assessments were made at 3 and 6 months using the Measure of Moral Distress-Healthcare Professionals (MMD-HP), Moral Distress Thermometer (MDT), and the Swedish Ethical Climate Questionnaire (SwECQ). Result Between-group analyses showed no significant differences in moral distress over time. Within-group analysis revealed that the intervention group scored lower moral distress concerning clinical causes at the patient level at the 3-month measurement point but returned to the same level as the control group at six months. The ethical climate was rated higher in the intervention group at 3 and 6 months. Conclusion Participation in ECG likely fosters shared values and an enhanced ethical climate, though no significant differences in moral distress were observed. Moral distress may persist despite interventions, but open dialogue and professional growth can foster moral resilience. This study found a positive relationship between an ethical climate and participation in ethics communication groups (ECG) using the ‘one to five method.’ However, the small sample size limited statistical power. Future research should include larger-scale, multicentre studies and qualitative research to explore experiences with ECG. Trial registration ClinicalTrials.gov : NCT05146102 (2021-11-05).